(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the role of digital technologies in physical education and sport training, focusing on their motivational, pedagogical, and ethical implications for learners and athletes. The study argues that digital tools such as wearable sensors, mobile applications, video analysis, learning platforms, heart-rate monitoring, GPS tracking, and artificial intelligence can improve feedback quality, individualize training load, support self-assessment, and strengthen engagement when they are embedded in a scientifically grounded pedagogical design. At the same time, digitalization can also create risks: data overload, superficial gamification, privacy violations, excessive comparison, coach dependence on metrics, and reduced intrinsic motivation. Using an IMRAD-based integrative review, the article synthesizes international physical activity policy documents, quality physical education principles, and recent research on digital technology in sport and physical education. The findings show that technology has positive educational value only when it serves clear learning outcomes, protects psychological safety, and remains subordinate to human-centered coaching. The article proposes a balanced model of digital sport pedagogy based on purpose, proportionality, feedback literacy, data ethics, inclusiveness, and long-term physical activity motivation.